Resistant - Palmer, Michael, 1942-2013 (New York : St. Martin's Press, 2014)
Duncan injures his leg while running, and the open wound is the perfect breeding ground for a deadly microbial. The government scientist tasked with finding a cure has been kidnapped. A shadowy group known as One Hundred Neighbors is using our health institutions as hostages and will stop at nothing to further their agenda.
Keywords: Centers for Disease Control and Prevention (U.S.) -- Fiction; Biological weapons -- Fiction; Atlanta (Ga.) -- Fiction; Suspense fiction; Medical novels